2017
DOI: 10.1186/s12917-017-1294-y
|View full text |Cite
|
Sign up to set email alerts
|

Neglected zoonotic agents in cattle abortion: tackling the difficult to grow bacteria

Abstract: Background Coxiella burnetii, Chlamydia abortus and Leptospira spp. are difficult to grow bacteria that play a role in bovine abortion, but their diagnosis is hampered by their obligate intracellular lifestyle (C. burnetii, C. abortus) or their lability (Leptospira spp.). Their importance is based on the contagious spread in food-producing animals, but also as zoonotic agents. In Switzerland, first-line routine bacteriological diagnostics in cattle abortions is regulated by national law and includes only basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 69 publications
1
63
1
7
Order By: Relevance
“…In total, 14 of 43 positive samples for Chlamydiales real-time PCR showed placentitis and necrosis, 12 of 14 samples mixed inflammation, and 7 of 14 samples vasculitis. 41 By PCR, all 91 investigated cases were negative for N. caninum. Another study examined the relevance of N. caninum as a bovine abortifacient pathogen in Swiss farms with abortion problems (n ¼ 113) compared with control farms (n ¼ 113).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In total, 14 of 43 positive samples for Chlamydiales real-time PCR showed placentitis and necrosis, 12 of 14 samples mixed inflammation, and 7 of 14 samples vasculitis. 41 By PCR, all 91 investigated cases were negative for N. caninum. Another study examined the relevance of N. caninum as a bovine abortifacient pathogen in Swiss farms with abortion problems (n ¼ 113) compared with control farms (n ¼ 113).…”
Section: Discussionmentioning
confidence: 95%
“…Of these, 35 positive samples of placentitis were present in 12 of 13 cases, necrosis was present 11 of 13 cases, mixed inflammatory infiltrates were found in 9 of 13 cases, and vasculitis was present in 5o f1 3c a s e s . 41 The diagnostic investigation of abortion is a stepwise process, which includes collection of appropriate samples, recording of a complete case history, macroscopic examination, microbiologic investigations,a sw e l la sh i s t o p a t h o l o g ya n d molecular analyses. Linking molecular results to macroscopic and/or microscopic findings is crucial to confirm the cause of abortion and to prevent false-positive results.…”
Section: Discussionmentioning
confidence: 99%
“…Although serological evidence of exposure to C. burnetii has already been reported in cattle in Europe (CZAPLICKI et al, 2009;AGGER et al, 2010;BOTTCHER et al, 2011;GACHE et al, 2017;RYAN et al, 2018;VARELA-CASTRO et al, 2018;VIDAL et al, 2017;SOFTIC et al, 2018), Asia (CETINKAYA et al, 2000NOKHODIAN et al, 2016), North America (MCQUISTON et al, 2005 and Africa (KAMGA-WALADJO et al, 2010;SCOLAMACCHIA et al, 2010), there are few data on seroprevalence to this agent in ruminants in Brazil. In this regard, while Guimarães et al (2017) found a seropositivity rate of 2% for C. burnetii among sheep sampled in the state of Piauí, northeast of Brazil, Oliveira et al (2018) found a seroprevalence of 55.1% in a herd of goats with history of reproductive disorders in the state of Alagoas, Northeast of Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Untersuchungen zu Abortursachen bei Rindern aus der Schweiz [19] ergaben mit 15,9 % maternalen Blutproben mit Nachweis von Coxiella burnetii-Ak eine etwas geringere Seroprävalenz als in der vorliegenden Arbeit mit 21 %. Es konnten jedoch bei 38,5 % der Schweizer Tiere Ak gegen Chlamydia abortus nachgewiesen werden, während in der vorliegenden Studie alle maternalen Blutproben für Chlamydia abortus-Ak negativ waren.…”
Section: Introductionunclassified
“…Bei der Interpretation einzelner Ak-Nachweise in maternalen Blutproben von Einzeltieren ist darauf zu achten, dass diese einen Hinweis auf eine Exposition mit einem spezifischen Pathogen oder einem Impfantigen geben, jedoch keine Auskunft über den Zeitpunkt [5] [19]. So konnte bei gesunden Kühen eine vergleichbare Coxiella burnetii-Seroprävalenz nachgewiesen werden wie bei Tieren mit Abortproblematik [19].…”
Section: Introductionunclassified